Elite Greco-Roman wrestlers' mental conditioning model - Maydokina, L. G.; Kokurin, A. V.; Kornishina, R. V. (Theory and Practice of Physical Culture, 2018)
In order to support progress of the Russian Federation on the global sport arenas, the relevant policies need to be further pursued to secure sustainable growth of the national professional sports. These policies have been supported by the relevant legal and regulatory provisions and sport management agencies. To facilitate further progress and competitive successes, a special emphasis in the existing athletic training systems needs to be made on the mental conditioning tools and models. Objective of the study was to rate the elite national Greco-Roman wrestlers` mental fitness and test the special mental conditioning model designed for the elite sport excellence stage. The study was designed to include the following three stages: (1) fact-finding stage to test the pre-experimental mental fitness rates of the elite Greco-Roman wrestlers; (2) piloting stage to develop and pilot a special mental conditioning model (including theoretical and practical modules) on a sample of elite Greco-Roman wrestlers; and (3) progress rating stage to rate the post- versus pre-experimental mental fitness of the sample. The study analyses detailed content, design and benefits of the proposed special mental conditioning model for elite Greco-Roman wrestlers.